The Relationship Between Self-Disclosure and Loneliness Among Early Adults Who Play the Game Roblox - Royen, Yolanda; Rinaldi (INDONESIAN COUNSELING AND PSYCHOLOGY, 2026)
The development of online games as virtual social interaction spaces, such as Roblox, allows individuals to engage in self-disclosure; however, it does not necessarily fulfill emotional closeness needs and may lead to loneliness. This study aims to examine the relationship between self-disclosure and loneliness among early adults who play Roblox. This research employed a quantitative method with a correlational approach. The sample consisted of 153 respondents selected using a purposive sampling technique, all of whom were early adults who play Roblox. Data were collected using a self-disclosure scale modified based on DeVito’s theory and a loneliness scale modified based on Russell’s theory. Data analysis was conducted using Pearson correlation. The results of the descriptive analysis indicated that the levels of self-disclosure and loneliness among respondents were in the moderate category. The findings revealed a significant positive relationship between self-disclosure and loneliness, with a correlation coefficient of r = 0.471 and a significance value of p = 0.001 (p < 0.05). These findings suggest that self-disclosure in the context of online gaming is not always associated with lower levels of loneliness, as digital interactions may not optimally fulfill emotional closeness needs. Therefore, self-disclosure has a significant relationship with loneliness among early adults who play Roblox in this study.